An Analytical – Comparative Economic Study of Cultivating Tomato in Soil and soilless culture in greenhouse - سليمان محمد; منذر خدام; بديع سمرة (Latakia University Journal -Biological Sciences Series, 2023)
This study was carried out in Marqiah village in Tartous governorate, during the spring growing of the year (2020-2021). Tomato (hybrid Bustuna) were planted in soil culture in a greenhouse covered with polyethylene, and same hybrid were planted in soilless culture in a greenhouse covered with polyethylene, perlite and black pumice were used as planting medium with 40% for perlite, the plants were not grafted and pruning was on one stem. this research aimed to compare between the cultivation of tomato in soil and soilless culture, to reveal its preference, through quantitative and qualitative indicators. The results of this study showed that total fixed costs of cultivation in soilless culture were higher (7967000 SP) compared to total fixed costs of cultivation in soil culture (5874000 SP). though, the plants were grown in soilless culture outperformed by all qualitative and quantitative indicators over plants grown in soil culture, and the productivity of the plant in soilless culture reached to 10 kg/plant, and to 5 kg/plant in soil culture, the net profit for soilless culture reached to 3664218 SP, and to 1029,968 SP in soil culture.